The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/cjas.1298
|View full text |Cite
|
Sign up to set email alerts
|

LEAD ‐ Leadership effectiveness, motivation, and culture in Africa: Lessons from Egypt, Ghana, Kenya, Nigeria, and Uganda

Abstract: This exploratory study considers an African perspective on leadership behaviour and motivation in Ghana, Egypt, Kenya, Nigeria, and Uganda using the Delphi Technique with a small sample of corporate, community, and religious leaders. Focus group sessions with working people (nonleaders) then followed. The findings indicate that vision, commitment, honesty, goal-orientation, and humour were descriptors of effective leadership. Further, it was found that the quest for justice, extrinsic benefits, and service to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Six stakeholder groups (72 participants) representing a 72 per cent response rate (100 invites issued) participated in the Delphi from February to June 2011 (see Table I). Senjali et al (2014) had similar sample sizes in their study (Round 1-61 participants and Round 2-46 participants). The aim was to have varied representation from stakeholder industries and geographic locations, not equal numbers in each group, with the focus on panel members’ cumulative knowledge and experience of mobile banking.…”
Section: Methodsmentioning
confidence: 99%
“…Six stakeholder groups (72 participants) representing a 72 per cent response rate (100 invites issued) participated in the Delphi from February to June 2011 (see Table I). Senjali et al (2014) had similar sample sizes in their study (Round 1-61 participants and Round 2-46 participants). The aim was to have varied representation from stakeholder industries and geographic locations, not equal numbers in each group, with the focus on panel members’ cumulative knowledge and experience of mobile banking.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative data that were collected from the first phase of the research project were analysed and concepts were identified. 1 Data collected came from African countries (Senaji et al, 2014) including Egypt, Ghana, Kenya, Nigeria, and Uganda (N = 94). Similarly, data were collected from Caribbean countries (Holder et al, 2014) and included participants (N = 42) from Barbados, Trinidad and Tobago, St. Vincent and the Grenadines, St. Lucia, and Jamaica.…”
Section: Phase 1: Initial Measure Development Using Qualitative Methomentioning
confidence: 99%
“…Overall, the findings from the Delphi technique and focus groups suggest that there was a preference for the ubuntu approach to leadership (Senaji, Metwally, Sejjaaka, et al, 2014). According to Ncube (2010), there are six steps to the ubuntu leadership philosophy: (1) setting the example and demonstrating the way; (2) inspiring a shared vision among followers that offers direction for others in a communal approach; (3) seeking opportunities to promote change through people and the use of consensus-decision making; (4) building relationships with others that promote interconnectedness and interdependency; (5) possessing a collectivist mindset that focuses on teamwork and a noncompetitive environment; and (6) building innovation and empowering others through continuous development of human potential, mentoring, and building relationships.…”
Section: Putting An Emic-etic-emic Cycle Into Practice: the Lead Projectmentioning
confidence: 99%
“…Participants from Ghana agreed that an effective leader “leads by example” and “walks the talk.” Similarly, the participants from Uganda noted that an effective leader “guides/leads/coaches/directs” and “takes action.” Second, participants from Ghana, Kenya, and Uganda highlighted the importance of inspiring a shared vision among followers and offering direction to others. In Ghana, participants noted that an effective leader “inspires” and “setting standards/goals.” Similarly, participants in Kenya stated that an effective leader “inspires,” “is goal oriented/achieves the goals of the team,” and “articulates/communicates goals/vision.” Participants in Uganda also stated that an effective leader “inspires” and has a “vision.” Third, participants from Ghana also stated the importance of “building a team spirit.” Finally, participants from Egypt, Kenya, and Nigeria agreed that it was important that leaders work with and take care of other people including employees and members of society (Senaji, Metwally, Sejjaaka, et al, 2014). The role of spirituality and connection to one’s ancestors, aspects of the ubuntu philosophy, were also discussed.…”
Section: Putting An Emic-etic-emic Cycle Into Practice: the Lead Projectmentioning
confidence: 99%
See 1 more Smart Citation